2022
DOI: 10.1590/s2175-97902022e201196
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Medication Errors in King Fahad Hospital Madina Saudi Arabia

Abstract: This study aimed to evaluate the incidence of medication errors over a period of one year in King Fahad Hospital Madina Saudi Arabia. This retrospective, cross-sectional study was conducted over a period of one year from 2018 January to 2018 December using patient's records. King Fahad Hospital in Madina was selected for the study center. Data collected include the number and types of errors, severity, location of errors, errors by profession, and errors occurred in the medical wards. Statistical analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Additionally, 58.2% of pharmacists were more likely to report an incident in which they were involved. These findings were consistent with findings in other studies that stated that patients had not reported MEs due to concerns about taking blame from patients, colleagues, or hospitals [ 11 ]. This finding urges the need for hospital management to facilitate positive and non-blame cultures for reporting MEs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, 58.2% of pharmacists were more likely to report an incident in which they were involved. These findings were consistent with findings in other studies that stated that patients had not reported MEs due to concerns about taking blame from patients, colleagues, or hospitals [ 11 ]. This finding urges the need for hospital management to facilitate positive and non-blame cultures for reporting MEs.…”
Section: Discussionsupporting
confidence: 92%
“…This is understandable from the fact that most of the pharmacists working in the Kingdom are males. Moreover, females are mostly reluctant to take part in activities such as surveys and interviews because of cultural constraints in Saudi Arabia [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations